Standardizing Compound Skill Tests (Physical – Motor) For Some Artistic Skills Of Volleyball Premier Players - Saba, Ahmed; Sattar, Kahlil; Dari, Ahmed (Journal of Physical Education, 2018)
Standardizing Compound Skill Tests (Physical – Motor) For Some Artistic Skills Of Volleyball Premier PlayersThe importance of the research lies in standardizing compound skill tests (physical – motor) of some artistic volleyball skills as well as concluding standards and criteria for the final tests. The research aimed at standardizing these tests. The researchers used the descriptive method. The subjects were (69) elite volleyball players and compound tests were conducted on them. The results showed that the tests were simple and suitable for the final tests. the researchers concluded criteria and standards for the compound tests. They recommended using these standards and criteria for evaluating volleyball players as well as updating these standards according the players' abilities.Keywords: physical, motor, tests, volleyball